Odpowiedzi

2010-02-02T21:06:46+01:00
6x-17y=11//6
-5x+15y=10

x=-2i5/6y+1i5/6
-5(-2i5/6y+1i5/6)+15y=10
14 i 1/6y-9i1/6+15y=10
19i1/6y=19i1/6 //19i1/6
y=1
-5x+15*1=10
-5x+15=10
-5x=-5 //(-5
x=1


2x-3y=6
y-2x=2

y=2+2x
2x-3(2+2x)=6
2x-6-6x=6
-4x=12 //(-4
x=-3

y-2*(-3)=2
y+6=2
y=-4


12x-6y=6
7x+y=8
y=8-7x
12x-6(8-7x)=6
12x-48-42x=6
-30x=54//(-30)
x=-1 i4/5

y=8-(-1i4/5)
y=9 i 4/5
2010-02-02T21:47:17+01:00
A)

6x-17y=11
-5x+15y=10/:(-5)

6x-17y=11
x-3y=-2

6x-17y=11
x=-2+3y

6(-2+3y)-17y=11
x=-2+3y

12+18y-17y=11
x=-2+3y

y=23
x=-2+3*23

y=23
x=67

b)

2x-3y=6
y-2x=2

2x-3y=6
y=2+2x

2x-3(2+2x)=6
y=2+2x

2x-6-6x=6
y=2+2x

-4x=12
y=2+2x

x=-3
y=2+2*(-3)

x=-3
y=4


c)

12x-6y=6/:6
7x+y=8

2x-y=1
7x+y=8

y=-1+2x
7x-1+2x=8

y=-1+2x
9x=9

y=-1+2x
x=1

y=-1+2*1
x=1

y=1
x=1